Properties of the endogenous components of the thioredoxin system in the psychrophilic eubacterium Pseudoalteromonas haloplanktis TAC 125 - FALASCA P.; EVANGELISTA G.; COTUGNO R.; MARCO S.; MASULLO M.; DE VENDITTIS E.; RAIMO, Gennaro (Extremophiles, 2012)
The endogenous components of the thioredoxin system in the Antarctic eubacterium Pseudoalteromonas haloplanktis have been purified and characterised. The temperature dependence of the activities sustained by thioredoxin (PhTrx) and thioredoxin reductase (PhTrxR) pointed to their adaptation in the cold growth environment. PhTrxR was purified as a flavoenzyme and its activity was significantly enhanced in the presence of molar concentration of monovalent cations. The energetics of the partial reactions leading to the whole electron transfer from NADPH to the target protein substrate in the reconstituted thioredoxin system was also investigated.While the initial electron transfer from NADPH to PhTrxR was energetically favoured, the final passage to the heterologous protein substrate enhanced the energetic barrier of the whole process. The energy of activation of the heat inactivation process essentially reflected the psychrophilic origin of PhTrxR.Vice versa, PhTrx possessed an exceptional heat resistance (half-life, 4.4 h at 95 C), ranking this protein among the most thermostable enzymes reported so far in psychrophiles. PhTrxR was covalently modified by glutathione, mainly by its oxidised or nitrosylated forms.Amutagenic analysis realised on three non catalytic cysteines of the flavoenzyme allowed the identification of C303 as the target for the S-glutathionylation reaction.